Ustilaginoidin D Induces Acute Toxicity and Hepatotoxicity in Mice - Bo Wang; Xiaolong Bai; Min Zhang; Xiangxiang Liu; Muhammad Zulqar Nain Dara; Lingjing Liu; Mingming Ou; Dayong Li; Jiyang Wang; Ling Liu; Wenxian Sun (Toxins)
Ustilaginoidin D is a type of bis-naphtho-γ-pyrone mycotoxin produced by Ustilaginoidea virens, the causal agent of rice false smut. Although previous studies have demonstrated the inhibitory effect of ustilaginoidin D on ATP synthesis and cancer cell growth in mice, its specific health risks remain unclear. Here, we reveal that ustilaginoidin D is highly toxic to mice with an LD50 value of 213 mg /kg·bw. Dose-dependent weight loss and liver damage were observed, accompanied by altered markers of liver cell damage, including the enzyme activities of alanine aminotransferase and aspartate aminotransferase and the content of glutathione in mouse liver. RNA-seq analysis of liver tissues from mice treated with 150 mg of ustilaginoidin D/kg·bw identified significant changes in gene expression profiles, with differentially expressed genes enriched in cancer-related pathways, hypertrophic cardiomyopathy, and metabolic pathways. RT-qPCR data are highly consistent with transcriptome analysis in expression profiles of 22 chemical-carcinogenesis-associated genes. These findings indicate that ustilaginoidin D induces acute toxicity and liver dysfunction in mice, raising serious concerns about its threat to human health.